Effect of erosive media on microhardness and fracture toughness of CAD-CAM dental materials - Alaaeldin Elraggal; Rania Afifi; Islam Abdelraheem (BMC, 2022)
Abstract Background Erosive acids might create surface flaws and deteriorate the mechanical properties of CAD-CAM materials. This invitro study aimed to investigate the effect of simulated gastric HCl and extrinsic erosive acids on surface microhardness and fracture toughness of CAD-CAM materials. Methods 400 bar-shaped specimens (17×4×2 mm3) were prepared from 4 different CAD-CAM dental materials (n = 100/group); monolithic zirconia (Ceramill Zolid HT+, Amanngirbach, Austria), lithium disilicate ceramic (IPS e.max CAD, Ivoclar Vivadent, Liechtenstein), nanohybrid resin composite (Grandio Blocs, VOCO) and polymer-infiltrated glass network (Vita Enamic, VITA Zahnfabrik). Specimens from each material type were further subdivided into 5 groups (n = 20) according to the erosive media applied (simulated gastric HCl, white wine, Coca-Cola®, orange juice, and artificial saliva that served as a control). Specimens were immersed for 24 h in an incubator at 37 ℃, then ultrasonically cleaned in distilled water and air-dried. Half of the specimens were tested for Vickers microhardness (VHN) at parameters of 500 gf for 10 s, while the rest of the specimens underwent 3-point flexure till fracture. Fractured surfaces were examined under a scanning electron microscope (SEM) for fracture toughness (KIC) calculation using the quantitative fractographic analysis method. Data collected were statistically analyzed using two-way analysis of variance (α = 0.05) after verification of data normality and homogeneity of variances. Results Erosive media created surface flaws that lowered the surface microhardness of the material and initiated the fracture pattern under different loads according to material type. The material type was a more predominant factor than erosive media that affected either the microhardness or the fracture toughness of CAD-CAM dental materials. The highest VHN and KIC values were found among Ceramill Zolid HT+ groups followed by IPS e.max CAD and Grandio Blocs regardless of the erosive media employed. Erosive media significantly reduced the VHN and KIC in Vita Enamic specimens compared to the rest of the material types. Conclusion All CAD-CAM materials used, except Vita Enamic, showed high resistance against the erosive acids indicating higher longevity of the material in patients frequently exposed to either extrinsic or intrinsic acid.